Comparing sequential organ failure assessment score, acute physiology and chronic health evaluation II, modified acute physiology and chronic health evaluation II, simplified acute physiology score II and poisoning severity score for outcome prediction of pesticide poisoned patients admitted to the intensive care unit - Gholamali Dorooshi; Shiva Samsamshariat; Farzad Gheshlaghi; Shafeajafar Zoofaghari; Akbar Hasanzadeh; Saeed Abbasi; Nastaran Eizadi-Mood (Wolters Kluwer Medknow Publications, 2023)
Objective: This study aimed to assess the severity of poisoning, various scoring systems, including Sequential Organ Failure Assessment (SOFA) score, acute physiology and chronic health evaluation II (APACHE II), Simplified Acute Physiology Score (SAPS II), Modified APACHE II, and poisoning severity score (PSS) were used. In this study, we compared the predictive value of these scoring systems on the outcome of pesticide-poisoned patients. Methods: This is a cross-sectional study of pesticide-poisoned patients (140 patients) who were admitted to the intensive care unit (ICU) of Khorshid Hospital, Isfahan, Iran, between January 2015 and 2019. The area under the receiver operating characteristic (AUC) curve and the predictive value of scoring systems were compared. Findings: Poisoning was higher in the male population (72.8%). The causes of poisoning were paraquat, (38.6%), aluminum phosphide, (32.1%), and organophosphate, (29.3%). The mean age of the patients was 33.9 years. Most patients (79.3%) attempted suicide. The mortality rate was 46.43%. The mean of "SOFA score," "APACHE II," "SAPS II," "Modified APACHE II," and "PSS" was 5.9; 15.7; 30.02; 15.8; and 1.9, respectively. There was a significant difference in the mean of all scoring systems for outcome prediction. Among all scoring systems, the SAPS II score with the cutoff point (16.5) had the best criteria for outcome prediction (AUC (0.831 ± 0.037), sensitivity (83.1%, 95% confidence interval [CI]: [71.7-91.2]), specificity (75.7%, 95% CI: [64.3-84.9]), positive predictive values (75.0%, 95% CI: [66.4-82.0]), negative predictive values (83.6%, 95% CI: [74.5-89.9]). Conclusion: The SAPS II scoring system may be a suitable indicator for outcome predictions in pesticide-poisoned patients in the ICU.